Initial breakdown and fast leaders in lightning discharges producing long‐lasting disturbances of the lower ionosphere. Issue 6 (28th June 2016) - Kotovsky, D. A.; Moore, R. C.; Zhu, Y.; Tran, M. D.; Rakov, V. A.; Pilkey, J. T.; Caicedo, J. A.; Hare, B.; Jordan, D. M.; Uman, M. A.
Abstract: The recent discovery of long recovery, early VLF scattering events (LOREs) indicates that the electric field changes from lightning discharges are capable of producing long‐lasting disturbances (up to tens of minutes) in the upper mesosphere and lower ionosphere. Comparison of lightning mapping array, broadband (up to 10 MHz) electric field, and VLF (∼300 Hz to 42 kHz) magnetic field measurements shows that the field changes produced by initial breakdown (IB) processes and the following leaders in natural, cloud‐to‐ground lightning discharges are detectable in VLF magnetic field measurements at long distances. IB radiation has been detected in VLF for lightning discharges occurring up to 2630 km away from the VLF observing station. Radio atmospherics associated with 52 LOREs, 51 regular recovery events, and 3098 flashes detected by National Lightning Detection Network and/or GLD360 were examined for IB radiation occurring up to 15 ms before the return stroke. Our analysis reveals that in contrast to regular recovery early VLF events, LOREs are strongly associated with lightning discharges which exhibit an intense IB process and a fast first leader (typical duration <4 ms). These experimental results demonstrate that initial breakdown and leader processes are indicators of discharge properties highly relevant to the total energy transfer between lightning discharges and the middle/upper atmosphere. Key Points: Radiation from IB processes are measured in VLF magnetic fields up to 2630 km away LOREs are strongly associated with lightning exhibiting intense IB and fast first leaders Observed properties of LORE causative discharges do not signify association with any particular TLE